History of Iskcon (International Society for Krishna Consciousness) Distribution in Belarus - Karassyova, Svetlana (Religions, 2022)
Based on several scientific publications, a limited number of news from the 1980s up until 2021 and a series of in-depth interviews with devotees in 2006-2021, the authors of the paper managed to restore the history of Bengal Vaishnavism distribution in Belarus for the first time. Specific attributes of its introduction to the country were: (1) philosophical requests from the local citizens, not immigration of its original bearers; (2) a long period of spontaneous distribution in the form of personal involvement with Vaishnava ideas and, hence, late institutionalization of the movement. The main stages of Vaishnavism development in Belarus were distinguished: (1) 1980s, the Soviet period: introduction of Vaishnava ideas and practices within individual self-identification of the members of small groups; (2) 1990s, the post-Soviet period: forming organizational structure of the International Society for Krishna Consciousness (ISKCON) in Belarus; (3) 2000s: spiritual and administrative crises and reformation of the systems of administration and practice creation of the institute of curating the newly converted devotees; (4) 2010s: search for and establishment of the new models of serving, the out-of-temple bhakti practice, in particular; further popularization of the Vaishnava movement and community in Belarus. The main source of information on the history of Vaishnavism distribution in Belarus were in-depth interviews with the members of the community standing at its origin.